Proximal Femoral Focal Deficiency/Congenital Femoral Deficiency: Evaluation and Management. Issue 13 (1st July 2022) - Nossov, Sarah B.; Hollin, Ilene L.; Phillips, Jessica; Franklin, Corinna C.
Abstract : Proximal focal femoral deficiency is a congenital transverse deficiency in which the femur is globally smaller with a typical proximal deformity at the hip that may include distal involvement of knees, leg, and feet. Congenital femoral deficiency (CFD) describes a broader spectrum of longitudinal deficiency inclusive of proximal focal femoral deficiency. CFD may also include lateral distal femoral hypoplasia, knee cruciate ligament deficiency, rotational instability, patellar dislocation, fibular hemimelia, ray absence, and contralateral limb involvement. Treatment intends to maximize function by limb equalization and deformity correction ranging from nonsurgical management using prosthetics to amputation and may include lengthening, shortening, and complex limb reconstruction. Management decisions depend on overall severity and the patient and family's preferences and priorities. Owing to its complexity, CFD is best treated by clinicians with considerable deformity treatment experience who can help guide decision making and embark on a treatment course that will maximize the functional outcome.